KOMPARASI CAPITAL ASSET PRICING MODEL DAN FAMA-FRENCH THREE FACTOR MODEL DALAM MEMPREDIKSI RETURN SAHAM - Ratna Dewi, Ni Putu Desy; Suartana, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.03.TAHUN 2018, 2018)
This study aims to compare the ability of CAPM and FF3FM in predicting stock return in Indonesia Stock Exchange. Population of this study is companies listed on the Indonesia Stock Exchange which are included in the Kompas 100 Index in the period of 2012 - 2016. The results show that market risk premium variable has a positive effect to return on six portfolios formed in CAPM and FF3FM. The variable size premium has a positive effect on S/H, S/M, and S/L portfolio return and has negative effect on portfolio return of B/H, B/M and B/L. The book to market premium variables have a positive effect on B/H, S/H and S/M portfolio returns and have a negative effect on B/L and S/L portfolio returns. While book to market premium has no effect on B/M portfolio return. The value of adjusted R square CAPM and FF3FM indicates that FF3FM ability in explaining return is better than CAPM.